Reducing beam aberrations of mechanical scanning transmit-array antennas - Matos, S. A. (2022)
There is a new demand for high gain antennas capable of achieving wide-angle beam steering in the microwave and millimeter wave (mmW) regimes. This work focuses on transmit-array (TA) antennas that steer the beam using only in-plane displacement of the TA or feed. We showed in previous works that., for some applications., this solution can be a viable alternative to the more costly electronic beam steering of phased arrays. However., it is necessary to balance the trade-offs between several factors such as gain., beam aberrations., antenna size., maximum scanning angle and the complexity of the mechanical steering system. This communication surveys different techniques that we developed to improve the overall scanning performance of these antennas.